The Use Of African Medicines In The Treatment Of Ḓorobo (Gonerrhoea), Among Female Youth - Isreal Siema; Thizwilondi Madima; Favour Siema (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The aim of this study was to explore the use of African medicines in the treatment of ḓorobo (Gonerrhoea), among female youth. Sexually transmitted infections are a major problem in South Africa. The Department of Health shows that most cases of sexual transmitted disease are reported each year. Currently there is lack of documentation to substantiate assertions regarding indigenous health care methods of the African communities relating to sexually transmitted infections. The objectives of the study were as follows; to explore the use of African indigenous medicine in the treatment of ḓorobo, the study adopted an African Healing Theories. The study used a qualitative research design and was exploratory in nature. Data was generated using semi-structured interviews as data collection instruments and analysed thematically. Purposive sampling was employed to select participants. The study discovered that most of the people uses African indigenous medicine for their daily health care needs in the treatment of ḓorobo in rural society. Moreso, African indigenous medicine is used by many people as primary health care since it is cheap and easily accessible, but it is said that it has some difficulties since it does not conform to the health standards of the country.